Peningkatan Kreatifitas Umkm Dan Kompetensi Wirausaha Melalui Edukasi Ekspor - Vivi Iswanti Nursyirwan; Sasmita Sari Ardaninggar; Asih Handayani (Universitas Pamulang, 2022)
Micro, small and medium enterprises (MSMEs) are the backbone of a nation's economy. However, the journey to becoming an important pillar of the national economy is not without obstacles. The author's observation sees that MSMEs are constrained by HR management, especially with regard to the competence of MSME HR. In the current VUCA era, competence is important for SMEs. In addition, another important thing is the marketing of MSME products. Go-Export is part of international marketing that needs to be socialized to MSME actors so that MSME actors at least get knowledge, skills and in the end can form relevant attitudes to support their business performance. The results of our observations show that many MSMEs have adapted well to grow, but on the other hand, we also find that many MSMEs do not know